1994
DOI: 10.1093/carcin/15.12.2747
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of oval cells into duct-like cells in preneoplastic liver of rats placed on a choline-deficient diet supplemented with ethionine

Abstract: Feeding male Wistar rats a choline-deficient diet containing 0.07% DL-ethionine (CDE diet) for up to 5 weeks results in the production of two distinct non-parenchymal cell populations, oval and duct-like cells. These cells can undergo replication and display different patterns of expression of glutathione S-transferases (GSTs) and pyruvate kinases (PKs). Oval cells were first detected around the periportal region after 1 week of CDE treatment and infiltrated the parenchyma after 2 weeks. Duct-like structures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 0 publications
7
61
0
Order By: Relevance
“…[32][33][34] Interestingly, the loss of IFN␥ signaling leads to a reduction in MPK ϩ oval cells, but not A6 ϩ oval cells. In our hands, A6 staining is confined to bile ducts in normal liver and mainly ductal and periductal oval cells in CDE-treated liver.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Interestingly, the loss of IFN␥ signaling leads to a reduction in MPK ϩ oval cells, but not A6 ϩ oval cells. In our hands, A6 staining is confined to bile ducts in normal liver and mainly ductal and periductal oval cells in CDE-treated liver.…”
Section: Discussionmentioning
confidence: 99%
“…13,20 When oval cells are isolated from animals placed on a choline-deficient, ethionine-supplemented diet, they rapidly deteriorate in culture, suggesting that exogenous factors are required for their survival and proliferation. 13 In the current human study, oval cells were often found in close association with fibrous tissue in the liver, often proliferating along the tracts from the expanded portal regions and along the limiting plates surrounding regenerative nodules. In addition, oval cells were often observed in close association with inflammatory cells, particularly in patients with hepatitis C. These observations suggest that cytokines or other factors produced by inflammatory Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15]20,21 The marker M2-PK has been found to be the most reliable marker for oval cells in our laboratory because it does not stain ductal cells as -GST does and it is not expressed in some adult hepatocytes in the same manner as ␣-fetoprotein. [13][14][15] M2-PK is detected in oval cells of adult liver. 15 We have observed that infiltrating lymphocytes in chronic hepatitis C infection can also exhibit some staining for M2-PK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with our observation that oval cells differentiate into bile duct cells in vivo , as shown by GST and PK immunohistochemistry. 16 …”
Section: Oval Cells Are a Heterogeneous Cell Compartmentmentioning
confidence: 99%